Male and Female Youth’s Opportunities to Attend Higher Education: Gender Equality Perspective in the Village - Ni Wayan Desi Ratna Sari; Luh Putu Artini; Dewa Putu Ramendra (Syntax Corporation, 2026)
This study discusses gender inequality in access to higher education among male and female youth in rural communities. Although education is a fundamental right for both men and women, social and cultural practices in many villages still prioritize males in obtaining higher educational opportunities. Economic limitations, patriarchal values, and traditional perceptions regarding gender roles often influence parents’ decisions in supporting their children’s education. Therefore, this research aims to analyze the opportunities of male and female youth to continue higher education from a gender equality perspective in the village context. This study employed a qualitative descriptive approach conducted in a village in Sekotong, West Lombok, Indonesia. The participants consisted of 26 individuals, including 10 parents and 16 students (8 male and 8 female students). Data were collected through in-depth interviews and analyzed using transcription, coding, and thematic analysis. The findings reveal that parents generally provide stronger support for sons to pursue higher education because men are considered future family breadwinners and decision-makers. In contrast, daughters are often expected to focus on domestic responsibilities after marriage. Economic hardship also contributes to the unequal educational opportunities experienced by female youth. In conclusion, gender inequality in rural education remains strongly influenced by patriarchal culture and financial limitations, which continue to restrict equal access to higher education for women.